Applications of neuroimaging in information science: Challenges and opportunities. Issue 1 (2013) - Gwizdka, Jacek; Mostafa, Javed; Moshfeghi, Yashar; Bergman, Ofer; Pollick, Frank E.
Abstract: This panel will discuss opportunities and challenges involved in applying cognitive neuroscience and neuroimaging in information science. The panelists will discuss lessons learned from related disciplines and will consider how neuroimaging tools, such as fMRI, fNIRS, and EEG, could contribute to information science.